Distribución de bacterias potencialmente fijadoras de nitrógeno y su relación con parámetros fisicoquímicos en suelos con tres coberturas vegetales en el sur de la Amazonia colombiana - Mantilla-Paredes, Andrea (2009)
Potentially nitrogen-fixing microaerobic and aerobic bacteria were isolated from several Colombian Amazon soils (for-est, pastures and chagras) and two landscapes (floodable and non floodable areas). The abundance and distri-bution of bacteria were evaluated, as well as their relationship with soil physical and chemical characteristics. Landscape had a direct influence on the abundance of the microaerobic bacteria, with higher numbers in forest and pasture soils in non-floodable zones. The aerobic isolates (N=51) were grouped into 19 morphologies, with the highest numbers found in forest soil in floodable zones. A higher number of aerobic morphologies was shared among forest sites (Nonmetric Multidimensional Scaling and Analysis of Similarity p<0.05), and 40% of the distribution was explained by lime percentage and Al concentration.